Indonesian National Army Unites Building Villages from a Corporate Social Responsibility Perspective - Prakosa, Chandra Ariyadi (Journal of International Conference Proceedings, 2024)
The Indonesian National Army Unites Building Villages (INAUBV) program as a social responsibility program carried out by the INA organization can be oriented as well as the Corporate Social Responsibility (CSR) program carried out by companies. The research was conducted in Sukoharjo Regency in 2021-2023. The research method is a case study. Sampling used Purposive Sampling. Research data uses primary and secondary data. Data collection through observation, in-depth interviews, Focus Group Discussions (FGD), and documentation. Data validation uses triangulation of sources and methods. Data analysis uses an interactive analysis model, which consists of: data reduction, data presentation and drawing conclusions. The research results concluded that according to the perspective of the CSR concept, the implementation of the INAUBV program meets the following principles: (a) Accountability, as a form of organizational (INA) responsibility for community problems; (b) Transparency, involving related agencies and the community in program implementation and reporting; (c) Ethical behavior, trying to establish harmonious relationships with various parties, including society; (d) Respect for stakeholder needs, involving relevant agencies and the community; (e) Respect for legal regulations, because it is carried out based on the INA Law; (f) Respect for international behavioral norms by adopting CSR programs; (g) Respect for human rights, increasing equitable development, because it prioritizes disadvantaged areas.Â Keywords: INA, INAUBV, CSR.